Depois de uma tragédia: família e emigração em Gonzaga, MG - Almeida, Alexandra Cristina Gomes de (Universidade Federal de São Carlos, 2011)
This dissertation addresses issues of emigration flow in the city of Gonzaga (MG). The city was featured in the international media world in consequence of the death of a citizen in September 2005, Jean Charles de Menezes. The young man was killed in a London subway station (England) after the British police have mistaken for a suspected terrorist, the event resumed debate on the problematic conditions which thousands of immigrants are exposed. From the anthropological perspective, the survey reports the social dynamics of the city, focusing on the notions of family and local traditions. So this ethnography describes families in their organization and values, which influence emigration flow.
Keywords: Antropologia; Migração; Etnografia; Doce, Rio, Vale (MG); CIENCIAS HUMANAS::ANTROPOLOGIA